A Mild Multistep Conversion of N-Protected α-Amino Acids into N-Protected β3-Amino Acids Utilizing the Nef Reaction - Sleebs, Brad E.; Nguyen, Nghi H.; Hughes, Andrew B. (Synlett, 2013)
Current methods of homologation of α-amino acids to β-amino acids have limitations. To overcome these shortfalls the Nef reaction has been utilized in the multistep synthesis of β3-amino acids from α-amino acids. In this approach, N-protected amino aldehydes, easily accessed from α-amino acids, were transformed into the N-protected γ-amino nitroalkanes. The Nef reaction was then used to smoothly convert the nitroalkanes into the corresponding N-protected β3-amino acids without notable racemization.
Keywords: amino acids; amino alcohols; amino aldehydes; nucleophilic addition; enantioselectivity